Magnetic Mineralogy of Speleothems From Tropical-Subtropical Sites of South America - Jaqueto, Plinio; Trindade, Ricardo I. F.; Feinberg, Joshua M.; Carmo, Janine; Novello, Valdir F.; Stríkis, Nicolás M.; Cruz, Francisco W.; Shimizu, Marília H.; Karmann, Ivo (Frontiers in Earth Science, 2021)
Fe-bearing minerals are a tiny fraction of the composition of speleothems. They have their origin in the karst system or are transported from the drainage basin into the cave. Recent studies on the magnetism of speleothems focused on the variations of their magnetic min-eralogy in specific time intervals, and are usually limited to a single sample. In this study, we describe a database of environmental magnetism parameters built from 22 stalagmites from different caves located in Brazil (South America) at different latitudes, comprising different climates and biomes. The magnetic signal observed in these stalagmites is dom-inated by low-coercivity minerals (~20 mT) whose magnetic properties resemble those of magnetite formed in pedogenic environments. Also, a comparison with few samples from soils and the carbonate from cave's walls shows a good agreement of the magnetic proper-ties of speleothems with those of soil samples, reinforcing previous suggestions that in (sub-)tropical regimes the dominant magnetic phase in speleothems is associated to the soil above the cave. Spearman’s rank correlation points to a positive strong correlation between magnetic concentration parameters (mass-normalized magnetic susceptibility, natural remanent magnetization, anhysteretic remanent magnetization and isothermal remanent magnetization). This implies that ultrafine ferrimagnetic minerals are the domi-nant phase in these (sub-)tropical karst systems, which extend across a diverse range of biomes. Although the samples are concentrated in the savannah biome (Cerrado) (~70%), comparison with other biomes shows a higher concentration of magnetic minerals in spe-leothem underlying savannahs and lower concentration in those underlying moist broad-leaf forests (Atlantic and Amazon biome) and dry forests (Caatinga). Thus, rainfall, bi-ome, and epikarst dynamics play an important role in the concentration of magnetic min-erals in speleothems in (sub-)tropical sites and indicate they can be an important target for paleoenvironmental research in cave systems.